O-114 Preimplantation genetic testing for monogenic diseases without necessary familial members. (30th June 2022) - Li, R
Abstract: Preimplantation genetic testing for monogenic diseases (PGT-M) is available for any single gene defects theoretically, as long as the disease-causing locus has been unequivocally identified. However, PGT-M has faced great challenges for couples with more than one genetic mutation, de novo mutations or without essential family members for linkage analysis. In order to overcome these challenges, we developed a comprehensive strategy which includes preimplantation genetic testing for aneuploidies (PGT-A) and chromosomal structural rearrangements (PGT-SR) study, as well as monogenic diagnosis study for couples bearing de novo mutations or without necessary familial members. The innovation of our strategy is to use the gamete (polar body or single sperm) or embryo as proband for linkage analyses (GEPLA) to detect an embryo's carrier status. GEPLA strategy uses affected embryo as proband or gametes carrying mutant alleles as proband for SNP linkage analyses, that were suitable for all types of patients mentioned above. Using this novel developed method, nine autosomal dominant polycystic kidney disease (ADPKD) couples with either de novo mutation or without a positive family history were recruited. Moreover, other two couples with single gene disorders (SMA and NF2) which lack of essential family members for linkage analysis including de novo mutation, and also combined with reciprocal translocation were recruited too. For nine ADPKD couples, a total of 34 embryos from 13 PGT-M cycles were examined and two couples were successfully delivered healthy babies. For the other two couples, 15 embryos were screened, and two embryos were determined as free of the monogenic disease and specific chromosomal abnormalities created by reciprocal translocations. This study provides a creative approach for embryo diagnosis of patients with de novo mutations or patients lacking of essential family members for linkage analysis, and even for reciprocal chromosome translocation concurrently.